Home automation using bluetooth technology - Ahmad Thibraani, Termizi (2007)
The world has witnessed significant advancement of technologies over the past decade. Those advance technologies existed to suit human’s desire to make life easy and less complicated. Home automation is a system that is designed to enable user to “control” the house with only a few hits on the computer keyboard. Various “intelligent” appliances, i.e., microwave ovens, air-conditioners, washing machines and home theatres are set to realize the concept of a smart home. With home automation system it becomes possible to control home appliances, which can be interconnected and monitored using a single Microchip PIC16F877A microcontroller through a Personal Area Network (PAN) in home environment. This project focuses on the application of Bluetooth technology in home automation and networking environment. A network that is built in this project contains a master module and a slave module. The slave communicates with the master through a Bluetooth connection.